The effect of various aerobic exercises on the endurance and some physiological variables among fitness training practitioners of at (30-35) years old - Ahmed Saeed, Taiseer; Khalid Yasser, Omar; Hashim Fenjan, Falih (International Journal of Psychosocial Rehabilitation, 2020)
The research sample consisted of 16 trainees, who were randomly selected. The researchers used the experimental method. The proposed exercises for the two experimental groups were applied. The study aimed to prepare various aerobic exercises such as treadmill, bicycle, stairs and elliptical And a comparison between a group practice different exercises to develop endurance and a second train using an exercise on the mobile traffic device, and knowledge of the effect of Walt Mrbnat on endurance and the maximum consumption prisoner and pure energy, and after the application of exercise , the researchers reached the most important conclusions of the emergence rate differences in research variables. The first experimental group in the research variables, which indicates the effectiveness of various aerobic exercises.